Validity of quantifying sensation of fishing reel using transmission error instead of sensory human evaluation for face gear design - Tetsuo INOUE (The Japan Society of Mechanical Engineers, 2019)
This paper discusses the determination of tooth-flank modification on a face gear system in order to improve the handle rotational sensation of a fishing spinning reel (hereafter, fishing reel sensation) and quantification of it. The spinning reel considered in this study uses a face gear system. One of the advantages of a face gear system is that it offers good rotational tactile sensation. However, these systems have a high propensity for assembly errors. If the reel experiences an assembly error, vibration based on the gear-pair engagement occurs when the handle of the reel rotates. The vibration is transmitted to the angler’s finger via the handle. When the vibration is large, the angler feels discomfort, which ultimately has a large influence on the fishing reel sensation. Therefore, reducing gear vibration is our most important objective. It was previously reported that when the tooth flank of the face gear is shaped according to a transmission-error-controlled curve, the reel exhibits robustness against the influence of assembly errors. The report indicated that there is a relationship between the fishing reel sensation and the amplitude of transmission error. However, it did not indicate a relationship between the fishing reel sensation and the waveform of transmission error. Moreover, the amount and width of tooth-flank modification were not optimized in the previous studies. On the other hand, because the fishing reel sensation is conventionally evaluated by human judgment, it is ambiguous and inefficient. To solve these problems, the best factor and level for tooth-flank modification were derived according to a design method based on robust engineering. The fishing reel sensation was quantified by the Mahalanobis–Taguchi system of robust engineering with high correlation. Moreover, a suitable noise factor could be applied in robust design by the accurate measurement of the transmission error. Accordingly, the optimum condition for tooth-flank modification was identified experimentally. This report elucidates the relationship between the fishing reel sensation and the waveform of transmission error and proposes a quantification of the same. Consequently, the face gear design for improving the fishing reel sensation has been established by quantifying the fishing reel sensation using the transmission error instead of sensory human evaluation.